Estudio de caso: Evaluación y tratamiento psicológico de una fobia específica al cáncer en un participante en consejo genético oncológico. - Olivera, Helena (Psicooncología, 2005)
Genetic Counseling in Oncology has become an important tool for cancer prevention and early detection. The proccess tries to benefit people who attend specialized Units, but it can suppose a negative psychological impact due to the high risk perception of participants after the experience of oncological diagnosis of near relatives. A case of cancer phobia of a Genetic Counseling participant is exposed. A semiestructured interview and STAI and BDI questionnaires were used for the assessment. The intervention techniques included on treatment plan were: psychoeducation, cognitive reestructurig, relaxation,exposure, planning of activities, social skills training and emotion recognition and expression. Results obtained after 6 sessions showed a reduction on anxiety levels and an improvement on mood state. The utility of this techniques is guaranteed for the aims proposed with the patient.